Visible-light-driven photocatalytic H2 evolution over CdZnS nanocrystal solid solutions: interplay of twin structures, sulfur vacancies and sacrificial agents. Issue 7 (4th February 2020) - Huang, Hai-Bo; Fang, Zhi-Bin; Yu, Kai; Lü, Jian; Cao, Rong
Abstract : Twinning CdZnS solid solution nanocrystals with rich sulfur vacancies show enhanced photocatalytic activity and stability for water splitting. Abstract : In the perspective of visible-light-driven hydrogen evolution, photocatalysts with suitable band energy levels and wide-range responses are particularly promising. Herein, Cd x Zn1− x S ( x = 0.2, 0.4, 0.6 and 0.8) nanocrystal solid solutions (NCSSs), which integrated twinning crystal structures, rich sulfur vacancies and wurtzite-sphalerite phase-junctions all in one, were prepared via a facile hydrothermal method. With these features, the twinning Cd0.6 Zn0.4 S performed remarkable photocatalysis for H2 evolution (42.66 mmol h −1 g −1 ) in Na2 S/Na2 SO3 aqueous solution, the rate of which was 691 times higher than those of pristine twinning CdS nanocrystals. To the best of our knowledge, this was the highest performance of H2 evolution among the hitherto reported one-fold sulfide photocatalysts. Density functional theory (DFT) calculations suggested the formation of twinning crystal structures improved the separation of photogenerated electron–hole pairs. Meanwhile, stability of the Cd0.6 Zn0.4 S photocatalyst was largely enhanced due to the fast hole consumption by Na2 S/Na2 SO3 through sulfur vacancies. This work explores the interplay and mechanism of special structures, sulfur vacancies and catalytic conditions of twinning CdZnS NCSSs, and provides guidance for the design of highly efficient and stable metal-sulfide-based photocatalysts.